Genotype × Environment Interaction in Grass Pea (Lathyrus sativus L.) Lines. (26th May 2009) - Polignano, G. B.; Bisignano, V.; Tomaselli, V.; Uggenti, P.; Alba, V.; Della Gatta, C.
Abstract : Eight grass pea lines grown in three different seasons were evaluated for the stability of seed yield, 100 seeds weight, flowering time, plant height, and biomass. Significant differences existed among years, lines, and lines× years interaction for all traits except for 100 seeds weight. Two methods of multivariate analysis cluster and principal components were utilized to determine: firstly, whether a pattern existed among lines in their response across years and secondly to examine the relationships among them. In both analyses, each line was presented as a vector whose elements were given by the performance of lines in each year. The analyses used arranged the lines into groups that were differentiable in terms of performances and stability. Our results provide useful information to aid the choice of grass pea lines in the Mediterranean marginal areas.